Proton-Conducting Sulfonated Periodic Mesoporous Organosilica - Wagner, Tobias; Tiemann, Michael (Nanomaterials)
Proton exchange membranes (PEMs) are essential for fuel cells, yet conventional materials like Nafion suffer from humidity dependence and limited thermal stability. This study introduces sulfonated phenylene-bridged periodic mesoporous organosilicas (PMOs) as promising inorganic–organic hybrid PEMs, synthesized via surfactant-templating with varying alkyl chain lengths for different mesopore sizes. Post-synthetic functionalization involves nitration of phenylene moieties, reduction to amines, and ring-opening of propane or butane sultones to graft sulfonic acid groups via flexible spacers, achieving homogeneous distribution along pore walls. Post-functionalization is confirmed by powder X-ray diffraction (PXRD), revealing preserved 2D hexagonal p6mm ordering and phenylene stacking. N2 physisorption shows type IV isotherms with reduced pore volumes and pore sizes. 1H NMR is used to quantify functionalization degrees. Impedance spectroscopy on pressed pellets demonstrates proton conductivities up to 2 × 10−3 S cm−1 at 30 °C and 90% RH, depending on the functionalization degree, confirming sulfonic acid-mediated conduction.

DsRNA-based carriers with pH-tuneable release kinetics for effective control of Psylliodes chrysocephala - Moorlach, Benjamin W.; Epkenhans, Robert; Ju, Di; Ravidas, Banuja; Weinberger, Christian; Tiemann, Michael; Buente, Judith; Gaerner, Maik; Wortmann, Martin; Scholten, Stefan; Rostas, Michael; Keil, Waldemar; et al. (International Journal of Biological Macromolecules)
Spray-induced gene silencing (SIGS) employing double-stranded RNA (dsRNA) offers a promising, species-specific approach for protecting crops from insect pests such as the cabbage stem flea beetle (Psylliodes chrysocephala). However, the environmental instability of dsRNA presents a major limitation to its field application. In this study, we evaluate two distinct dsRNA formulation strategies for improved stability and delivery: a bottom-up approach using chitosan-based interpolyelectrolyte complexes (IPEC) and a top-down approach employing functionalized mesoporous silica carriers (SBA-15). Both systems were comprehensively characterized in terms of size, surface potential, porosity, and release behavior. The results revealed that IPECs exhibited release kinetics that were approximately one order of magnitude faster than those of SBA-15 across all tested conditions. The two formulations significantly improved dsRNA stability against UV and heat exposure compared to free dsRNA. In feeding assays with P. chrysocephala, both carriers achieved comparable gene silencing efficacy, though dsRNA@IPEC induced more immediate effects, while dsRNA@SBA-15 displayed delayed but ultimately stronger reduction in consumed leaf area, consistent with its slower release kinetics. We demonstrate that despite structural and mechanistic differences, both delivery platforms effectively stabilized and delivered dsRNA, and offered distinct advantages depending on application needs. This work highlights how formulation strategies are key to successful SIGS and supports the development of robust, field-adaptable formulation technologies for sustainable pest management.

Defect Structure-Performance Correlation in Eu³⁺@UiO-66: Design of Coordination Sites for Rapid Optical O₂ Sensing - Zhao, Zhenyu; Tiemann, Michael (Journal of Materials Chemistry C)
Defect engineering offers an effective route to tailor the local coordination environment, gas transport and excited-state processes in metal-organic frameworks (MOFs). We establish a quantitative structure-property relationship linking defect-modulated porosity...

Exploring feedstock structural components as predictors for physico-chemical biochar properties - Moser, Konstantin; Pfeifer, Christoph; Wopienka, Elisabeth; Voglar, Jure; Prašnikar, Anže; Likozar, Blaž; Weinberger, Christian; Tiemann, Michael; Çubuk, Dilara; Haslinger, Walter (Scientific Reports)
To further improve the capabilities necessary to accurately predict biochar properties based on feedstock characteristics, a study correlating feedstock structural components with biochar properties was conducted. To produce biochar, ten different biomass feedstocks were sourced mostly from Austria. The feedstocks gathered were spruce chips; woodchips from broad-leaved forestry; wheat bran; Japanese knotweed; walnut shells; screening overflow from composting; and residues from Mary thistle, rapeseed, hemp, and poppy flower processing. These feedstocks were pyrolyzed at 500 and 700 °C under nitrogen (N2) atmosphere in a customized muffle furnace. The feedstocks were analyzed for their lignin, hemicellulose, cellulose, fat content, and other properties. Mercury intrusion porosimetry (MIP) was performed on the biochar samples, with the highest documented intruded volume being 3.64 cm3/g. Elemental recoveries in the biochar samples were determined and correlated with feedstock structural components (FSC). Additionally, the water solubility of biochar nutrient elements was determined, with K showing the highest solubility of 35.5 ± 18.5% at 700 °C. Elemental recoveries of C/H/N/Cl showed significant correlations with FSC (e.g., Cl showed a significant and strong negative correlation with cellulose, r = − 0.874/p < 0.01). Intruded volume as well as K solubility also showed significant correlations. These results indicate that feedstock structural components can serve as predictors for more biochar properties than currently used in the literature, although the limited sample size requires further research to confirm the findings presented here.

Role of Irradiance in Light-Activated In2O3Gas Sensors: Why More Light Is Not Always Better - Voth, Sven; Zhao, Zhenyu; Baier, Dominik; Glass, Alexandra; Elgabarty, Hossam; Sandberg, Oskar J.; Grundmeier, Guido; Tiemann, Michael; Smått, Jan-Henrik; Anttu, Nicklas; de los Arcos, Teresa; Weinberger, Christian (ACS Sensors)
Light-assisted metal oxide-based chemiresistive gas sensors are widely explored for operation at relatively low temperatures, yet the investigation of the role of irradiance, as opposed to wavelength, remains underrepresented. Here, we systematically quantify the irradiance-dependent behavior of ordered mesoporous In2O3 under visible light illumination. Photoconductivity measurements reveal two distinct irradiance regimes consistent with trap-limited transport at low power and recombination- or saturation-limited transport at high power. Gas sensing experiments towards CO and H2 show a pronounced non-monotonic response, reaching maximum responses of 0.74 for 135 ppm CO at 67 mW cm−2 and 0.64 for 90 ppm H2 at 11 mW cm−2, followed by strong suppression at higher irradiance. Illumination also accelerated the response kinetics. At 60 ppm, t90 decreases from 96 to 12 s for CO and 141 to 27 s for H2, corresponding to an 8- and 5-fold faster response time, respectively. Near-ambient pressure-XPS under controlled atmosphere and density functional theory calculations indicate defect-mediated excitation. Oxygen vacancy states and illumination-induced modification of surface oxygen species govern this behavior. The results establish irradiance as a critical mechanistic parameter that determines whether In2O3 operates in a surface-controlled or bulk photoconductive regime. These findings highlight the need to explicitly optimize and report irradiance in illuminated gas sensor studies, and not only the power consumption of the light source.
Keywords: resistive gas sensing; indium oxide; photoactivation; irradiance; photoconductivity; charge carrier dynamics; oxygen vacancies

Water in the Micropores of CPO-27 Metal-Organic Frameworks: A Comprehensive Study - Kloß, Marvin; Weinberger, Christian; Tiemann, Michael (Microporous and Mesoporous Materials)
The metal-organic framework CPO-27 exhibits free coordination sites (open metal sites) and can be prepared with a wide range of metals that influence its properties. It is therefore an intriguing structure to study sorption phenomena. We analyze the water resistance and sorption behavior of these frameworks, with particular attention to the sorption mechanism in detail and the structure of the confined water molecules. For this purpose, we use manometric water vapor sorption analysis and FTIR spectroscopy. The respective metal center orchestrates both the adsorption behavior and the arrangement of the water molecules in the micropores of the framework. The extent to which water molecules form hydrogen bonds (with each other and with framework oxygen atoms) plays a crucial role in the stability of the framework towards water. Water adsorption is governed by the coordination of water molecules to the open metal sites (except for CPO-27-Cu) and subsequent H-bonding. A stepwise adsorption of water is observed, with significant differences depending on the choice of metal.

Oxygen‐dependent Photoluminescence and Electrical Conductance of Zinc Tin Oxide (ZTO): A Modified Stern‐Volmer Description - Kothe, Linda; Klippstein, Josefin; Kloß, Marvin; Wengenroth, Marc; Poeplau, Michael; Ester, Stephan; Tiemann, Michael (ChemPhysChem)
Zinc tin oxide (ZTO) is investigated as a photoluminescent sensor for oxygen (O2); chemisorbed oxygen quenches the luminescence intensity. At the same time, ZTO is also studied as a resistive sensor; being an n‐type semiconductor, its electrical conductance decreases by adsorption of oxygen. Both phenomena can be exploited for quantitative O2 sensing. The respective sensor responses can be described by the same modified Stern‐Volmer model that distinguishes between accessible and non‐accessible luminescence centers or charge carriers, respectively. The impact of the temperature is studied in the range from room temperature up to 150 °C.

Temperature Studies of Zinc Tin Oxide Photoluminescence for Optical O2 Sensing - Kothe, Linda; Kloß, Marvin; Wagner, Tobias; Wengenroth, Marc; Poeplau, Michael; Ester, Stephan; Tiemann, Michael (The Journal of Physical Chemistry C)

Water-assisted proton conductivity and a magnetic study of heterotrinuclear oxalate-bridged compounds: molecular precursors for the Mn2CrO4 spinel - Lozančić, Ana; Burazer, Sanja; Wagner, Tobias; Molčanov, Krešimir; Pajić, Damir; Androš Dubraja, Lidija; Tiemann, Michael; Jurić, Marijana (Journal of Materials Chemistry C)
Novel oxalate-bridged heterotrinuclear complexes [A][Mn2Cr(bpy)2(H2O)2Cl2(C2O4)3] (A = (CH3)2(C2H5)NH+ (1) and (CH3)(C2H5)2NH+ (2); bpy = 2,2′-bipyridine) were synthesized using an aqueous solution of [A]3[Cr(C2O4)3] as a building block in reaction with Mn2+ ions and with the addition of the N-donor ligand bipyridine. The isostructural heterometallic complex salts were characterized by single-crystal and powder X-ray diffraction, infrared and impedance spectroscopy, thermal analysis and magnetization measurements. The trinuclear anion [{Mn(bpy)(H2O)Cl(μ-C2O4)}2Cr(C2O4)]− consists of two [Mn(bpy)(H2O)Cl]+ units bridged by the [Cr(C2O4)3]3− anion, which acts as a bidentate ligand towards each of the manganese atoms. The anions are hydrogen bonded to each other via coordinated chloride anions, water molecules and oxygen oxalate atoms, resulting in two-dimensional (2D) hydrogen bonding layers. Compounds exhibit water-assisted proton conductivity behaviour, which was investigated at different temperatures and relative humidities (RH). At 25 °C, an increase in RH from 60% to 93% resulted in an obvious proton conducting switch from 9.1 × 10−11 to 5.6 × 10−5 S cm−1 for 1 and from 7.4 × 10−10 to 1.8 × 10−6 S cm−1 for 2, corresponding to high on/off ratios of about 106 for 1 and 104 for 2. In situ powder X-ray diffraction (PXRD) analysis showed that unit cell parameters of compounds 1 and 2 slightly increase when exposed to humid conditions. This confirmed that incorporation of water molecules into structures with pores and voids causes the proton conductivity switching phenomenon. Magnetic susceptibility measurements indicate a ferromagnetic interaction between Cr3+ and Mn2+ ions bridged by the bis(bidentate) oxalate group. The prepared compounds 1 and 2 were explored as single-source precursors for the formation of spinel oxide by their thermal treatment. With increasing temperature, the spinel composition changed according to the formula Mn1+xCr2–xO4 (0 ≤ x ≤ 1), where x = 0.7 at 500 °C and x = 1 at 900 °C when tet[MnII]oct[MnIIICrIII]O4 is formed. The (micro)structure, morphology, and optical properties of spinel Mn2CrO4 were characterized by PXRD, scanning electron microscopy and UV-Vis diffuse reflectance spectroscopy. The photocatalytic activity of this oxide in degradation of the methylene blue dye under Vis irradiation without and with the support of hydrogen peroxide was further investigated.

Fast‐Responding O2 Gas Sensor Based on Luminescent Europium Metal‐Organic Frameworks (MOF‐76) - Zhao, Zhenyu; Weinberger, Christian; Steube, Jakob; Bauer, Matthias; Brehm, Martin; Tiemann, Michael (Advanced Functional Materials)
The increasing demand for advanced sensing technologies drives the development of chemical sensors using innovative materials. In gas sensing, optical sensors are often used to detect gases such as CO, NOx, and O2. Oxygen sensors typically incorporate dyes into oxygen-permeable matrices like polymers, silica, or zeolites. Alternatively, semiconductor surface chemistry can enable O2 detection. However, these approaches are often limited by slow response and recovery times and low selectivity, restricting their practical applications. The metal-organic framework MOF-76(Eu) and its yttrium-modified variant, MOF-76(Eu/Y) are reported to exhibit highly reversible and fast optical responses to varying O2 concentrations. Time-resolved emission measurements are performed over short (seconds) and long (hours) timescales using N2 and synthetic air mixtures. Cross-sensitivity to humidity is analyzed. Multichannel scaling photon-counting experiments confirm quenching at the linker level, as the emission lifetime remains nearly constant. Yttrium significantly improves stability and performance at room temperature. Structural and optical changes induced by yttrium are investigated. Additionally, MIL-78(Eu), another Eu-BTC-based MOF with a different coordination environment, is synthesized. Unlike MOF-76(Eu), MIL-78(Eu) exhibits distinct optical properties but lacks a reversible response to O2. These results highlight the potential of MOF-76-based materials for high-performance O2 sensing.

Disaggregation at High Volume Exclusion: An “Overcrowding” Effect - Koch, Leon; Baier, Dominik; Rajput, Satyendra; König, Benedikt; Tiemann, Michael; Ebbinghaus, Simon; Nayar, Divya; Huber, Klaus (The Journal of Physical Chemistry B)

Fast‐Responding O2 Gas Sensor Based on Luminescent Europium Metal‐Organic Frameworks (MOF‐76) - Zhao, Zhenyu; Weinberger, Christian; Steube, Jakob; Bauer, Matthias; Brehm, Martin; Tiemann, Michael (Advanced Functional Materials)
Abstract The increasing demand for advanced sensing technologies drives the development of chemical sensors using innovative materials. In gas sensing, optical sensors are often used to detect gases such as CO, NO x , and O 2 . Oxygen sensors typically incorporate dyes into oxygen‐permeable matrices like polymers, silica, or zeolites. Alternatively, semiconductor surface chemistry can enable O 2 detection. However, these approaches are often limited by slow response and recovery times and low selectivity, restricting their practical applications. The metal‐organic framework MOF‐76(Eu) and its yttrium‐modified variant, MOF‐76(Eu/Y) are reported to exhibit highly reversible and fast optical responses to varying O 2 concentrations. Time‐resolved emission measurements are performed over short (seconds) and long (hours) timescales using N 2 and synthetic air mixtures. Cross‐sensitivity to humidity is analyzed. Multichannel scaling photon‐counting experiments confirm quenching at the linker level, as the emission lifetime remains nearly constant. Yttrium significantly improves stability and performance at room temperature. Structural and optical changes induced by yttrium are investigated. Additionally, MIL‐78(Eu), another Eu‐BTC‐based MOF with a different coordination environment, is synthesized. Unlike MOF‐76(Eu), MIL‐78(Eu) exhibits distinct optical properties but lacks a reversible response to O 2 . These results highlight the potential of MOF‐76‐based materials for high‐performance O 2 sensing.

Nontoxic and Rapid Chemical Bath Deposition for SnO2 Electron Transporting Layers in Perovskite Solar Cells - Grotevent, Matthias J.; Kothe, Linda; Lu, Yongli; Krajewska, Chantalle J.; Shih, Meng-Chen; Tan, Shaun; Tiemann, Michael; Bawendi, Moungi G. (Chemistry of Materials)

Selective H2 Gas Sensing Using ZIF-71/In-SnO2 Bilayer Sensors: A Size-Selective Molecular Sieving Approach - Baier, Dominik; Kieke, Laureen; Voth, Sven; Kloß, Marvin; Huck, Marten; Steinrück, Hans-Georg; Tiemann, Michael (ACS Sensors)

Electrochemical Removal of HF from Carbonate-based LiPF6-containing Li-ion Battery Electrolytes - Ge, Xiaokun; Huck, Marten; Kuhlmann, Andreas; Tiemann, Michael; Weinberger, Christian; Xu, Xiaodan; Zhao, Zhenyu; Steinrueck, Hans-Georg (Journal of The Electrochemical Society)
Due to the hydrolytic instability of LiPF6 in carbonate-based solvents, HF is a typical impurity in Li-ion battery electrolytes. HF significantly influences the performance of Li-ion batteries, for example by impacting the formation of the solid electrolyte interphase at the anode and by affecting transition metal dissolution at the cathode. Additionally, HF complicates studying fundamental interfacial electrochemistry of Li-ion battery electrolytes, such as direct anion reduction, because it is electrocatalytically relatively unstable, resulting in LiF passivation layers. Methods to selectively remove ppm levels of HF from LiPF6-containing carbonate-based electrolytes are limited. We introduce and benchmark a simple yet efficient electrochemical in situ method to selectively remove ppm amounts of HF from LiPF6-containing carbonate-based electrolytes. The basic idea is the application of a suitable potential to a high surface-area metallic electrode upon which only HF reacts (electrocatalytically) while all other electrolyte components are unaffected under the respective conditions.
Keywords: Materials Chemistry; Electrochemistry; Surfaces; Coatings and Films; Condensed Matter Physics; Renewable Energy; Sustainability and the Environment; Electronic; Optical and Magnetic Materials

Natural near field coupled leaky-mode resonant anti-reflection structures: the setae of Cataglyphis bombycina - Schwind, Bertram; Wu, Xia; Tiemann, Michael; Fabritius, Helge-Otto (Frontiers in Physics)
Leaky mode resonances of the setae of Cataglyphis bombycina are found to enhance the thermal emission of the animals by near field coupling to the chitinous exoskeleton. This is remarkable, as the setae are also an adaption to enhance the reflectivity in the visible wavelength range. Both effects are dependent on morphology, dimensions and spatial arrangement. These parameters were experimentally characterized and simulated by finite difference time domain simulations to elucidate the optical impact of the setae in the mid infrared range and the contribution of leaky mode resonances. This mode of action and the setae’s optical properties in the visible range explain evolutionary strains that led to the actual morphology and size of the setae.

Stabilisierung von O2-sensitiven Photolumineszenzsignalen durch Temperaturvariation - Kothe, Linda; Ester, Stephan; Poeplau, Michael; Wengenroth, Marc; Tiemann, Michael (Proceedings 22. GMA/ITG-Fachtagung Sensoren und Messsysteme 2024)
In dieser Arbeit werden Untersuchungen zur sauerstoffabhängigen Photolumineszenz von Zink-Zinn-Oxid-Partikeln präsentiert, welche perspektivisch für die optische Sauerstoffdetektion eingesetzt werden sollen. Zink-Zinn-Oxid zeigt eine sauerstoffabhängige Photolumineszenz im sichtbaren Spektralbereich und wird hier als eine photostabile Alternative zu den kommerziell verfügbaren metallorganischen Verbindungen vorgestellt. Der Fokus liegt dabei auf dem Einfluss der Temperatur auf die Sauerstoffsensitivität der Photolumineszenz. Wir zeigen, dass bereits leichte Temperaturerhöhungen zu einer signifikanten Verbesserung der Sauerstoffsensitivität der Photolumineszenz führen und gleichzeitig die Signalqualität erhöhen.

Gas Sensing with Nanoporous In2O3 under Cyclic Optical Activation: Machine Learning-Aided Classification of H2 and H2O - Baier, Dominik; Krüger, Alexander; Wagner, Thorsten; Tiemann, Michael; Weinberger, Christian (Chemosensors)
Clean hydrogen is a key aspect of carbon neutrality, necessitating robust methods for monitoring hydrogen concentration in critical infrastructures like pipelines or power plants. While semiconducting metal oxides such as In2O3 can monitor gas concentrations down to the ppm range, they often exhibit cross-sensitivity to other gases like H2O. In this study, we investigated whether cyclic optical illumination of a gas-sensitive In2O3 layer creates identifiable changes in a gas sensor´s electronic resistance that can be linked to H2 and H2O concentrations via machine learning. We exposed nanostructured In2O3 with a large surface area of 95 m2 g-1 to H2 concentrations (0-800 ppm) and relative humidity (0-70%) under cyclic activation utilizing blue light. The sensors were tested for 20 classes of gas combinations. A support vector machine achieved classification rates up to 92.0%, with reliable reproducibility (88.2 ± 2.7%) across five individual sensors using 10-fold cross-validation. Our findings suggest that cyclic optical activation can be used as a tool to classify H2 and H2O concentrations.
Keywords: resistive gas sensor; chemiresistor; semiconductor; metal oxide; In2O3; mesoporous; hydrogen; humidtiy; machine learning; sustainable

Water Sorption on Isoreticular CPO-27-Type MOFs: From Discrete Sorption Sites to Water-Bridge-Mediated Pore Condensation - Kloß, Marvin; Schäfers, Lara; Zhao, Zhenyu; Weinberger, Christian; Egold, Hans; Tiemann, Michael (Nanomaterials)
Pore engineering is commonly used to alter the properties of metal–organic frameworks. This is achieved by incorporating different linker molecules (L) into the structure, generating isoreticular frameworks. CPO-27, also named MOF-74, is a prototypical material for this approach, offering the potential to modify the size of its one-dimensional pore channels and the hydrophobicity of pore walls using various linker ligands during synthesis. Thermal activation of these materials yields accessible open metal sites (i.e., under-coordinated metal centers) at the pore walls, thus acting as strong primary binding sites for guest molecules, including water. We study the effect of the pore size and linker hydrophobicity within a series of Ni2+-based isoreticular frameworks (i.e., Ni2L, L = dhtp, dhip, dondc, bpp, bpm, tpp), analyzing their water sorption behavior and the water interactions in the confined pore space. For this purpose, we apply water vapor sorption analysis and Fourier transform infrared spectroscopy. In addition, defect degrees of all compounds are determined by thermogravimetric analysis and solution 1H nuclear magnetic resonance spectroscopy. We find that larger defect degrees affect the preferential sorption sites in Ni2dhtp, while no such indication is found for the other materials in our study. Instead, strong evidence is found for the formation of water bridges/chains between coordinating water molecules, as previously observed for hydrophobic porous carbons and mesoporous silica. This suggests similar sorption energies for additional water molecules in materials with larger pore sizes after saturation of the primary binding sites, resulting in more bulk-like water arrangements. Consequently, the sorption mechanism is driven by classical pore condensation through H-bonding anchor sites instead of sorption at discrete sites.

Understanding Hydration in CPO‐27 Metal‐Organic Frameworks: Strong Impact of the Chemical Nature of the Metal (Cu, Zn) - Kloß, Marvin; Beerbaum, Michael; Baier, Dominik; Weinberger, Christian; Zysk, Frederik; Elgabarty, Hossam; Kühne, Thomas D.; Tiemann, Michael (Advanced Materials Interfaces)
CPO‐27 is a metal‐organic framework (MOF) with coordinatively unsaturated metal centers (open metal sites). It is therefore an ideal host material for small guest molecules, including water. This opens up numerous possible applications, such as proton conduction, humidity sensing, water harvesting, or adsorption‐driven heat pumps. For all of these applications, profound knowledge of the adsorption and desorption of water in the micropores is mandatory. The hydration and water structure in CPO‐27‐M (M = Zn or Cu) is investigated using water vapor sorption, Fourier transform infrared (FTIR) spectroscopy, density functional theory (DFT) calculations, and molecular dynamics simulation. In the pores of CPO‐27‐Zn, water binds as a ligand to the Zn center. Additional water molecules are stepwise incorporated at defined positions, forming a network of H‐bonds with the framework and with each other. In CPO‐27‐Cu, hydration proceeds by an entirely different mechanism. Here, water does not coordinate to the metal center, but only forms H‐bonds with the framework; pore filling occurs mostly in a single step, with the open metal site remaining unoccupied. Water in the pores forms clusters with extensive intra‐cluster H‐bonding.